Inclusive Landscapes of Investigation - Skovsmose, Ole [UNESP] (Open Book Publishers, 2022)
By means of two examples, one concerning polygons and one concerning erosions of democracy, I characterise the conception of inclusive landscapes of investigation. These are teaching-learning environments that are accessible for everybody, and invite dialogue across differences. This brings me to refer to universal design, which provides a broader perspective on the construction of inclusive environments. Finally, I relate the concept of critique to the characteristics of inclusive landscapes of investigation.